(untitled) (The Review of Diabetic Studies, 2024)
Interprofessional collaboration (IPC) has become an essential pillar of modern healthcare delivery, particularly in highly specialized fields such as nursing, radiation therapy, and radiology. This comprehensive review synthesizes global evidence on the nature, determinants, and outcomes of collaborative practice among these professional groups. The study examines how interdisciplinary teamwork enhances clinical efficiency, care coordination, patient outcomes, and safety in diagnostic and therapeutic settings. Findings indicate that effective IPC is influenced by organizational culture, role clarity, communication practices, professional autonomy, and shared decision-making frameworks. Barriers, including hierarchical structures, limited understanding of professional roles, workload pressures, and resource constraints, continue to hinder optimal collaboration across many healthcare systems. Nevertheless, evidence shows that structured communication models, joint training programs, collaborative leadership approaches, and technological integration significantly improve teamwork and care delivery. The review concludes that strengthening interprofessional collaboration among nurses, radiation therapists, and radiology professionals is crucial for advancing patient-centered care, improving workflow efficiency, and supporting high-quality oncology and diagnostic services. Recommendations emphasize the need for institutional policies that foster collaborative environments, investment in interprofessional education, and ongoing evaluation of teamwork practices to ensure sustainable improvements in healthcare outcomes.